THE RELATIONSHIP BETWEEN KNOWLEDGE OF SCHEMATA AND TEXT COMPREHENSION A Survey at English Department of State University of Padang, 2010 - Tiarina, Yuli (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
This study is aimed at finding the relationship between knowledge of schemata and text comprehension. It was conducted at English Department of State University of Padang on the fifth semester in the academic year of 2009/2010.There were 38 students as the sample using cluster sampling technique. The instruments used were multiple choice tests. The quantitative data were analized by using simple correlation and regression. It was found that there is a relationship between knowledge of schemata and text comprehension. It means that someone who has good knowledge of schemata will have good text comprehension. The equation is Å¶ = 13.39 + 0.95X1. Its correlation coefficient is 0.6962. The knowledge of schemata gives contribution 48.47% to text comprehension. The findings can be beneficial for the teachers as a consideration that they can help students to activate their schemata in order to get good text comprehension. Key words/phrases: knowledge of schemata, text comprehension